Self-repairing rubbers comprising poly (glycerol monomethacrylate) borate complexes

By using a dynamic polymer (glycerin mononotomic acrylate) borate compounds in rubber compositions, it solves the problem that the self -repairing natural rubber in the existing technology is difficult to take into account the mechanical strength and self -repair efficiency. Rubber compositions with high mechanical strength and self -repairing performance are suitable for high -performance needs of tires.

CN119384457APending Publication Date: 2025-01-28BRIDGESTONE CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380047655.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-17
Filing Date
2023-06-15
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing self-repairing natural rubber is difficult to balance between mechanical strength and self-repair efficiency, and cannot meet the high mechanical strength and self-repair needs of tires.

Method used

By using a dynamic polymer (glycerin single -based methyl -based acrylate) borate compounds in rubber compositions, combined with the aggregation and borax cross -linking technology catalyzed by the CO (II) complex Performance rubber composition.

Benefits of technology

实现了固化橡胶的高机械强度和自修复性能,满足轮胎的高性能需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005191989040000081
    Figure BDA0005191989040000081
  • Figure BDA0005191989040000101
    Figure BDA0005191989040000101
  • Figure BDA0005191989040000121
    Figure BDA0005191989040000121
Patent Text Reader

Abstract

The present invention relates to a method of making a rubber composition comprising polymerizing glycerol monomethacrylate, cross-linking the obtained poly (glycerol monomethacrylate) with borax to form a poly (glycerol monomethacrylate) dynamic borate complex, and blending the complex with an additive. The invention further relates to a rubber composition, a cured rubber composition and a self-repairing tire using the rubber composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of self-repairing rubber, and in particular to a rubber composition comprising a dynamic poly(glycerol monomethacrylate) borate complex, a preparation method thereof, and use thereof in a self-repairing tire. Background Art

[0002] Self-healing natural rubber is known in the prior art. C. Xu et al., "Design of Self-Healing Supramolecular Rubbers by Introducing Ionic Cross-Links into Natural Rubber via a Controller Vulcanization", ACS Appl. Mater. Interfaces 2016, 8, 17728-17737, DOI: 10.1021 / acsami.6b05941, describe controlled peroxide-induced vulcanization to produce ionic crosslinks via polymerization of zinc dimethacrylate in natural rubber. In Ch.Xu et al., "Self-Healing Natural Rubber with Tailorable Mechanical Properties based Ionic Supramolecular Hybrid Network", ACS Appl.Mater.Interfaces 2017, 9, 29363-29373, DOI: 10.1021 / acsami.7b09997, the authors aim to enhance the performance of self-healing natural rubber by in-situ polymerization of excess zinc oxide (ZnO) and methacrylic acid in natural rubber to form zinc dimethacrylate. Although self-healing natural rubbers are known from these publications, their mechanical strength is poor.

[0003] The use of methacrylate macromonomers as "sulfur-free" RAFT agents in polymerization-induced self-assembly (PISA) systems is described by A. Lotierzo et al. in "Toward Sulfur-Free RAFT Polymerization Induced Self-Assembly", ACS Macro Lett. 2017, 6, 1438-1443, DOI: 10.1021 / acsmacrolett.7b00857. The preparation of polymers containing boronate dynamic covalent bonds is described in S. Tajbakhsh et al., "Recyclable Polymers with Boronic Ester Dynamic Bonds Prepared by Miniemulsion Polymerization", ACS Appl. Polym. Mater. 2021, 3, 3402-3415, DOI: 10.1021 / acsapm.1c00368.

[0004] Y. Chen et al. described thiol-containing borate esters for crosslinking self-healing styrene butadiene rubber (SBR) in "Covalently Cross-Linked Elastomers with Self-Healing and Malleable Abilities Enabled by Boronic Ester Bonds", ACS Appl. Mater. Interfaces 2018, 10, 24224-24231, DOI: 10.1021 / acsami.8b09863. In addition, in "Mechanically Robust, Self-Healable, and Reprocessable Elastomers Enabled by Dynamic Dual Cross-Links", Macromolecules 2019, 52, 3805-3812, DOI: 10.1021 / acs.macromol.9b00419, Y. Chen et al. described the covalent crosslinking of epoxidized natural rubber (ENR) with a borate crosslinker with a dithiol through a chemical reaction between epoxy and thiol groups.

[0005] N. Yang et al., “Polyvinyl Alcohol / Silk Fibroin / Borax Hydrogel Ionotronics: A Highly Stretchable, Self-Healable, and Biocompatible Sensing Platform”, ACS Appl. Mater. Interfaces 2019, 11, 23632-23638, DOI: 10.1021 / acsami.9b06920 reported a biocompatible ionic hydrogel made of polyvinyl alcohol, silk fibroin and borax, which can be used as a sensing platform for monitoring peripheral body movements. Summary of the invention

[0006] One object of the present invention is to provide a rubber composition which, in its cured state, offers improved self-healing properties and at the same time high mechanical strength, so that it can be used in tires.

[0007] Surprisingly, it was found that the use of a complex prepared by crosslinking an oligomer or polymer of glycerol monomethacrylate with borax in a rubber composition solves the trade-off between self-healing efficiency and mechanical strength in the cured rubber. The cured rubber is self-healing and simultaneously achieves high mechanical strength, which allows it to be used in tires.

[0008] Therefore, the present invention relates to a method for preparing a rubber composition, which method comprises at least the following steps: (A) polymerizing glycerol monomethacrylate in the presence of a Co(II) complex as a catalytic chain transfer agent to obtain poly(glycerol monomethacrylate), which is an oligomer or polymer of glycerol monomethacrylate and has a number average molecular weight (M n ) is in the range of from 160 to 3200 g / mol and preferably has a dispersion degree of Equal to or less than 4;

[0009] (B) cross-linking poly(glycerol monomethacrylate) with borax to obtain a poly(glycerol monomethacrylate) dynamic borate complex; and

[0010] (C) blending the poly(glycerol monomethacrylate) dynamic borate complex with a vulcanization activator system, a diene rubber, sulfur, and a vulcanization accelerator to prepare a rubber composition.

[0011] As used herein, the term "poly(glycerol monomethacrylate)" or "pGMMA" in abbreviated form means an ω-vinyl oligomer or polymer of glycerol monomethacrylate. As used herein, the term "poly(glycerol monomethacrylate)" is used interchangeably with the term "poly(glycerol monomethacrylate) oligomer".

[0012] In a preferred embodiment of the process, in step (A), the molecular weight of the poly(glycerol monomethacrylate) is controlled by the ratio of glycerol monomethacrylate to the Co(II) complex, in particular wherein a ratio of glycerol monomethacrylate to the Co(II) complex of 10 is used. 6 : 10 to 10 6 :180.

[0013] In other preferred embodiments of the process, the Co(II) complex is cobaloxime boron fluoride, in particular the Co(II) complex is bis[(difluoroboryl)-dimethylglyoxime]cobalt(II).

[0014] In a further preferred embodiment, poly(glycerol monomethacrylate) is mixed with borax in a weight ratio of 1.0:0.05 to 1.0:0.4 in step (B).

[0015] In a preferred embodiment of the process, in step (C), the poly(glycerol monomethacrylate) borate complex is blended with a vulcanization activator system that is zinc oxide and an organic acid. In a more preferred embodiment, the organic acid used is stearic acid, which forms a vulcanization activator complex with zinc oxide during processing. In another preferred embodiment of the process, the vulcanization activator system is a poly(zinc methacrylate)-zinc oxide activator (p(ZnMA) / ZnO) complex. Preferably, the organic acid used is an ω-vinyl oligomer of methacrylic acid, which is mixed with zinc oxide to form a poly(zinc methacrylate)-zinc oxide activator (p(ZnMA) / ZnO) complex before blending with diene rubber, sulfur and a vulcanization accelerator.

[0016] In a further preferred embodiment, the number average molecular weight (M) of poly(glycerol monomethacrylate) is n ) is in the range of from 160 to 3200 g / mol, preferably in the range of from 320 to 2400 g / mol. In other preferred embodiments, the dispersion degree of poly(glycerol monomethacrylate) Equal to or less than 4, preferably equal to or less than 2.

[0017] In other preferred embodiments, in step (C) the diene rubber is selected from the group consisting of natural rubber, isoprene rubber, styrene-butadiene rubber, butadiene rubber, and combinations thereof.

[0018] In an exemplary embodiment, the vulcanization accelerator in step (C) is based on a sulfenamide compound and / or a thiazole compound.

[0019] In a further preferred embodiment, fillers are additionally used in step (C), in particular wherein the amount of filler is 5.0 to 80 phr, based on 100 phr of diene rubber.

[0020] The present invention further relates to a rubber composition comprising

[0021] - a poly(glycerol monomethacrylate) dynamic borate complex obtained by polymerizing glycerol monomethacrylate in the presence of a Co(II) complex as a catalytic chain transfer agent to obtain an oligomer or polymer of glycerol monomethacrylate having a number average molecular weight (M n ) in the range of from 160 to 3200 g / mol, and crosslinking the poly(glycerol monomethacrylate) with borax;

[0022] -Vulcanization activator system;

[0023] -diene rubber;

[0024] - sulfur; and

[0025] -Vulcanization accelerator.

[0026] The preferred rubber composition of the present invention comprises

[0027] - a poly(glycerol monomethacrylate) dynamic borate complex obtained by polymerizing glycerol monomethacrylate in the presence of a Co(II) complex as a catalytic chain transfer agent to obtain a poly(glycerol monomethacrylate) which is an oligomer or polymer of glycerol monomethacrylate and has a number average molecular weight (Mn) in the range of from 160 to 3200 g / mol, and crosslinking the poly(glycerol monomethacrylate) with borax;

[0028] - zinc oxide and an organic acid, preferably zinc oxide and stearic acid;

[0029] -diene rubber;

[0030] - sulfur; and

[0031] -Vulcanization accelerator.

[0032] A further preferred rubber composition comprises

[0033] - a poly(glycerol monomethacrylate) dynamic borate complex obtained by polymerizing glycerol monomethacrylate in the presence of a Co(II) complex as a catalytic chain transfer agent to obtain a poly(glycerol monomethacrylate) which is an oligomer or polymer of glycerol monomethacrylate and has a number average molecular weight (Mn) in the range of from 160 to 3200 g / mol, and crosslinking the poly(glycerol monomethacrylate) with borax;

[0034] - poly(zinc methacrylate)-zinc oxide activator (p(ZnMA) / ZnO) complex;

[0035] -diene rubber;

[0036] - sulfur; and

[0037] -Vulcanization accelerator.

[0038] In a preferred embodiment, the rubber composition contains a filler, preferably in an amount of 5.0 to 80 phr, based on 100 phr of the diene rubber.

[0039] The present invention further provides a cured rubber or a cured rubber composition obtained by curing the above-mentioned rubber composition.

[0040] Furthermore, the present invention provides a self-repairing tire comprising a tire component, preferably a tread, produced by using the above-mentioned rubber composition.

[0041] All references herein to the unit "phr" refer to parts by weight per 100 parts by weight of rubber.

[0042] As used herein, the term "molecular weight", for example, number average molecular weight (M n ), refers to the determination by size exclusion chromatography (SEC), and preferably additionally by 1 H nuclear magnetic resonance (NMR) spectroscopy.

[0043] As used herein, the term "dispersity" refers to the molecular weight distribution and is determined by the following equation:

[0044]

[0045] Among them, M w is the weight average molecular weight, M n is the number average molecular weight.

[0046] Preferred embodiments of the invention are described in the following description, examples, figures and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1A reaction scheme for the formation of a dynamic boronate complex is shown.

[0048] Figure 2 Cure curves and tensile tests of the cured rubbers of Examples 1 to 4 are shown.

[0049] Figure 3 The mechanical properties of the cured rubbers of Examples 1 to 4 are shown.

[0050] Figure 4 DMA analysis of the cured rubbers of Examples 1 to 4 is shown.

[0051] Figure 5 The mechanical properties of the cured rubbers of Examples 5 and 6 are shown.

[0052] Figure 6 Tensile testing of the cured rubbers of Examples 7 to 9 is shown. DETAILED DESCRIPTION

[0053] The rubber composition according to the present invention is curable and at least comprises diene rubber, poly(glycerol monomethacrylate) dynamic borate complex, vulcanization activator system, sulphur, vulcanization accelerator, and preferably filler, wherein preferably vulcanization activator system is zinc oxide (ZnO) and organic acid. In a preferred embodiment, organic acid is stearic acid. In another preferred embodiment, organic acid is methacrylic acid ω-vinyl oligomer.

[0054] The diene rubber is preferably selected from natural rubber (NR), styrene-butadiene rubber (SBR), isoprene rubber, butadiene rubber (BR) or a combination thereof. Preferably, natural rubber (NR), styrene-butadiene rubber (SBR) or a combination thereof is used. A suitable blend is 80-90% by weight of natural rubber and 20-10% by weight of styrene-butadiene rubber, based on 100% by weight of rubber.

[0055] According to the present invention, the number average molecular weight (M) of the poly(glycerol monomethacrylate) dynamic borate complex is n ) in the range of from 160 to 3200 g / mol, especially the dispersion is equal to or less than 4. Preferably, M n In the range from 240 to 2400 g / mol, the dispersion Equal to or less than 2, more preferably M n In the range from 240 to 1600, the dispersion Less than 2. Molecular weights of 160 to 3200 g / mol correspond to degrees of polymerization of 2 to 40.

[0056] Poly(glycerol monomethacrylate) is produced by oligomerizing or polymerizing glycerol monomethacrylate by catalytic chain transfer (CCT) using a cobalt (II) complex as a catalyst, wherein the polymerization degree or molecular weight of the poly(glycerol monomethacrylate) can be controlled by the ratio of the monomer (glycerol monomethacrylate) and the catalyst.

[0057] An exemplary embodiment of the polymerization using bis[(difluoroboryl)-dimethylglyoxime]cobalt(II) (CoBF) as a catalyst is shown in Figure 1 wherein n represents the number of monomer units. Preferably, n is 2 to 15.

[0058] The cobalt (II) complex or catalyst can be any cobalt complex known in the art for catalyzing chain transfer polymerization (CCTP). Suitable catalysts are described in, for example, EP 1 295 922 A2, US 9 090 724 B2 and US 9 580 529 B2. Preferably, bis [(difluoroboryl) - dimethylglyoxime] cobalt (II) is used as the catalyst.

[0059] Poly(glycerol monomethacrylate) is cross-linked with borax to obtain dynamic borate esters, such as Figure 1 The reaction is preferably carried out in deionized water, preferably at ambient temperature. In a preferred embodiment, the water is then removed by lyophilization.

[0060] The poly(glycerol monomethacrylate) dynamic borate complex comprises a network of dynamic borate esters which, when added to a rubber composition, imparts self-healing properties to the cured rubber.

[0061] ZnO is commonly used as an additive in rubber compositions for tires because it acts as a vulcanization accelerator. In a preferred embodiment of the present invention, ZnO is added in combination with stearic acid and a zinc stearate salt is formed in situ. In the present invention, ZnO can be used in the form of zinc stearate or in the form of p(ZnMA) / ZnO. When p(ZnMA) / ZnO is used, a complex can be formed by mixing an ω-unsaturated oligomer of methacrylic acid with ZnO in water before mixing and then freeze-drying to form a dry complex.

[0062] Suitable fillers for rubber compositions are not limited and are known in the field of tire production. Exemplary fillers are carbon black, silica and combinations thereof. Carbon black and silica with a specific surface area are commercially available and can be used. Fillers are typically used in an amount of 5 phr to 80 phr, preferably 5 phr to 50 phr, more preferably 10 phr to 40 phr.

[0063] In the present invention, sulfur is used as a crosslinking agent in vulcanization. Sulfur provides covalent crosslinks in the cured rubber composition and contributes to the mechanical strength of the cured rubber.

[0064] Suitable vulcanization accelerators are based on sulfenamide compounds and / or thiazole compounds. Preferably, N-cyclohexyl-2-benzothiazolesulfenamide (known as CBS) or tetramethylthiurammonosulfide is used.

[0065] Rubber composition can comprise other additives, particularly the additive that is generally used for tire production in this area.Such additive is lubricant, pigment, activator, softener, plasticizer, antioxidant, fatty acid (such as stearic acid etc.).Usually, the total amount of these additives is no more than 10 wt % or no more than 10phr based on 100 wt % of rubber composition.

[0066] The present invention also provides the cured rubber composition or cured rubber obtained after curing the curable rubber composition of the present invention. Curing can be carried out as known in the art and is not limited. Suitable curing temperature is in the range of from 150 ℃ to 160 ℃.

[0067] The rubber composition of the present invention is particularly useful for producing one or more tire components or one or more rubber components of a self-repairing tire, including a tread or a tire casing (case) compound. In particular, the rubber composition is preferably used for the tread or tread portion of a self-repairing tire. Therefore, the present invention further provides a self-repairing tire comprising a tire component, more preferably a tread, produced by using the self-repairing rubber composition of the present invention. As known in the art, the tire component is produced by the rubber composition in a suitable device

[0068] The rubber composition of the present invention imparts self-repairing properties and high mechanical strength to the tire.

[0069] The following examples illustrate the invention without limiting the scope of protection.

[0070] Example

[0071] Examples 1 to 4

[0072] Examples 1 to 4 relate to different rubber compositions, which illustrate the effect of poly(glycerol monomethacrylate) dynamic borate complex on the self-healing and mechanical properties of the cured rubber.

[0073] The formulations used are shown in Table 1 below, where the values ​​relate to phr. The comparative formulation is CV1, which does not contain pGMMA-borax but otherwise comprises the same components in corresponding amounts.

[0074] Table 1

[0075]

[0076] The components shown are as follows.

[0077] NR: Natural Rubber.

[0078] pGMMA-borax: poly(glycerol monomethacrylate) (M n =1600 g / mol) and borax in a weight ratio of 10:1.

[0079] CBS: N-cyclohexyl-2-benzothiazolesulfenamide.

[0080] Sulfur: Commercially available sulfur used in tire production.

[0081] The indicated components were blended in a Haake PolyLab twin screw compounder at 40°C and 50 rpm. The curing properties and optimum curing time (t 90 The samples were then cured in a Collin P200 hot press at a temperature of 150°C and a pressure of 150 bar to their t 90 Curing time to form a 9×9cm sheet with a thickness of 1mm 2 membrane.

[0082] Figure 2 (a) Cure curves of the formulation of Table 1 obtained with MDR, and (b) tensile tests of CV1 and the formulation of Table 1 are shown. Mechanical properties were evaluated by measuring stress (MPa) versus impact strain (%) at a strain rate of 100 mm / min on a Shimadzu AGS-X tensile tester. The results are shown in Table 1 compared to a formulation without pGMMA-borax (CV1). Figure 2 middle.

[0083] Figure 3 The self-healing test in terms of recovery in % is further shown. These results were obtained by repeating the tensile test with specimens from each sample which had been cut in half with a scalpel and then overlapped over an area of ​​4 mm x 3 mm before being placed under a weight of 20 N at 80°C for 30 minutes or 2 hours. The percent recovery value was then calculated from the value obtained from the cut specimen relative to the uncut specimen.

[0084] The stress recovery values ​​and strain recovery values ​​of the cured rubbers of Examples 1 to 4 are shown in Table 2 below.

[0085] Table 2:

[0086]

[0087] Figure 4 Shown are DMA analyses of CV1 and the formulations of Table 1. These results were measured on a Tritec 2000DMA in tension mode at 1% strain and 5 Hz frequency over a temperature range of -80 and 100 °C.

[0088] Examples 5 and 6

[0089] Examples 5 and 6 relate to rubber compositions showing the effect of pGMMA-borax on rubber compositions containing additional pZnMA / ZnO salt (which is a preformed salt of pMAA and ZnO in a weight ratio of 1:1) as a cure activator. The formulations used are shown in Table 3 below.

[0090] Table 3:

[0091] PG5-pZnMA NR 100 pZnMA / ZnO 15 pGMMA-Borax 5 CBS 0.14 sulfur 0.7

[0092] The components as indicated were blended in the same manner as described in Examples 1 to 4.

[0093] The mechanical properties were evaluated by measuring stress (MPa) versus impact strain (%) at a strain rate of 100 mm / min on a Shimadzu AGS-X tensile tester. Figure 5 middle.

[0094] Examples 7 to 9

[0095] Examples 7 to 9 relate to rubber compositions showing the effect of adding carbon black N234 to compound PG20 as given in Examples 1 to 4. The detailed compositions are given in Table 4.

[0096] Table 4:

[0097] PG20 CB10 PG20 CB25 PG20 CB40 NR 100 100 100 ZnO 5 5 5 Stearic acid 1 1 1 pGMMA-Borax 20 20 20 CBS 0.14 0.14 0.14 sulfur 0.7 0.7 0.7 CB N234 10 25 40

[0098] The components given in Table 4 were blended as described in Examples 1 to 4. Their mechanical properties were again evaluated by measuring stress (MPa) versus impact strain (%) on a Shimadzu AGS-X tensile tester at a strain rate of 100 mm / min. The results are shown in Figure 6 In addition, the self-repairing efficiency was evaluated using the same method as described in Examples 1 to 4 and is given in Table 5.

[0099] Table 5:

[0100]

[0101] The results obtained indicate that the addition of dynamic borate complexes has a beneficial effect on the self-healing and mechanical properties of the cured rubber.

Claims

1. A method for preparing a rubber composition, comprising at least the following steps: (a) polymerizing glycerol monomethacrylate in the presence of a Co(II) complex as a catalytic chain transfer agent to obtain poly(glycerol monomethacrylate), which is an oligomer or polymer of glycerol monomethacrylate and has a number average molecular weight (M n ) is in the range of from 160 to 3200 g / mol and preferably has a dispersion degree of Equal to or less than 4; (B) cross-linking poly(glycerol monomethacrylate) with borax to obtain a poly(glycerol monomethacrylate) dynamic borate complex; and (C) blending the poly(glycerol monomethacrylate) dynamic borate complex with a vulcanization activator system, a diene rubber, sulfur, and a vulcanization accelerator to prepare a rubber composition.

2. The method according to claim 1, wherein: In step (A), the molecular weight of poly(glycerol monomethacrylate) is controlled by the ratio of glycerol monomethacrylate to Co(II) complex, in particular, the ratio of glycerol monomethacrylate to Co(II) complex is 10:

1. 6 : 10 to 10 6 :

180.

3. The method according to claim 1 or 2, wherein the Co(II) complex is cobaloxime boron fluoride, in particular wherein the Co(II) complex is bis[(difluoroboryl)-dimethylglyoxime]cobalt(II).

4. The method according to any one of claims 1 to 3, wherein: In step (B), poly(glycerol monomethacrylate) and borax are mixed in a weight ratio of 1.0:0.05 to 1.0:0.

4.

5. The method according to any one of claims 1 to 4, wherein: In step (C), the vulcanization activator system is zinc oxide and an organic acid, preferably the vulcanization activator system is zinc oxide and stearic acid.

6. The method according to any one of claims 1 to 4, wherein: In step (C), the vulcanization activator system is a poly(zinc methacrylate)-zinc oxide (p(ZnMA) / ZnO) complex.

7. The method according to any one of claims 1 to 6, wherein: In step (C), the diene rubber is selected from the group consisting of natural rubber, isoprene rubber, styrene-butadiene rubber, butadiene rubber, and combinations thereof.

8. The method according to any one of claims 1 to 7, wherein: In step (C), the amount of the poly(glycerol monomethacrylate) dynamic borate complex is 5.0 to 40 phr based on 100 phr of the diene rubber.

9. The method according to any one of claims 1 to 8, wherein: In step (C), a filler is additionally used, in particular wherein the amount of filler is 5.0 to 80 phr, based on 100 phr of the diene rubber.

10. A rubber composition comprising: - a poly(glycerol monomethacrylate) dynamic borate complex obtained by polymerizing glycerol monomethacrylate in the presence of a Co(II) complex as a catalytic chain transfer agent to obtain an oligomer or polymer of glycerol monomethacrylate having a number average molecular weight (M n ) in the range of from 160 to 3200 g / mol, and crosslinking the poly(glycerol monomethacrylate) with borax; -Vulcanization activator system; -diene rubber; - sulfur; and -Vulcanization accelerator.

11. The rubber composition according to claim 10, wherein the vulcanization activator system is zinc oxide and an organic acid, preferably the vulcanization activator system is zinc oxide and stearic acid.

12. The rubber composition of claim 10, wherein the cure activator system is a poly(zinc methacrylate)-zinc oxide (p(ZnMA) / ZnO) complex.

13. The rubber composition according to any one of claims 10 to 12, wherein the rubber composition additionally comprises a filler, in particular in an amount ranging from 5.0 to 80 phr, based on 100 phr of diene rubber.

14. A cured rubber composition obtainable by curing a rubber composition prepared according to the method defined in any one of claims 1 to 9 or a rubber composition according to any one of claims 10 to 13.

15. A self-repairing tire comprising a tire component, preferably a tread, prepared by using the rubber composition prepared by the method defined in any one of claims 1 to 9 or the rubber composition according to any one of claims 10 to 13.

Citation Information

Patent Citations

  • Pigment dispersing resins

    EP1295922A2

  • Low viscosity suspending vinyl copolymers

    US9090724B2

  • Preparation of low-viscosity polymers

    US9580529B2